NORMATIVITY OF INTERNATIONAL LAW - Dajović, Goran (Pravni zapisi, 2021)
In “The Nature of International Law”, Miodrag Jovanović, generally speaking, tries to explain the concept of international law. He analyzes few typical characteristics of the prototype concept of law (institutionality, normativity, coercion and justice-aptness), and then he looks at contemporary international law through “the lenses” of these characteristics. The article pays special attention to his analysis of the normativity of (international) law. The main intention is not to criticize Jovanović’s theses about the normativity of law, as such, but to point out that they are not the best possible framework for explaining the normativity of international law. Therefore, a different and more appropriate conceptual framework is presented than the one he offered in the key of Raz’s idea of ​​legal norms as exclusionary reasons for action and practical rationality. This framework is grounded on Hart’s well-known idea of ​​an internal point of view. The presented argumentation shows that within such a framework, the normativity of international law could be better explained and understood, and also it seems that certain ingrained intuitions about international law fit well into it.